An Overview of Drug Discovery and Molecular Docking (International Journal of Food and Nutritional Sciences, 2022)
CADD is growing rapidly and succeeding. Pharmaceutical companies utilise CADDD forresearch lead discovery, as do academics. Structural informatics, genomics, and proteomicshave accelerated the hunt for novel medications. Docking methods and molecular active siteshave been studied for two decades. Computational methods are used in hit discovery, leadoptimization, and other drug development steps. Each docking step adds complexity.Docking places small molecules in the enzyme's active region. In addition to these methods,scoring functions analyse molecular interactions with possible targets to quantify biologicalactivity. Docking tools and computational methods can show the molecule's 3D structure anddocking score. Molecular Docking, a kind of structure-based virtual screening (SBVS),inserts small molecules into a target structure in various locations, conformations, andorientations. Protein-ligand docking has several applications. Structure-based drug design(SBDD), lead optimization, and biochemical pathway assessment in de novo drug discoverymake it a hot investigation field. This review describes molecular docking. Molecular docking Estimating the binding mode and afinity of the complex improves molecularrecognition docking to find new therapeutic leads.